2014
DOI: 10.2134/cm-2013-0039-rs
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide and Fungicide Wheat Seed Treatment Improves Wheat Grain Yields in the U.S. Southern Plains

Abstract: Hard red winter wheat (Triticum aestivum L.) in the U.S. Southern Plains is subject to yield losses due to a wide range of pests. Foliar‐applied pesticides are commonly used to control damaging insect populations, but rescue application of foliar pesticides generally occurs at or above threshold infestation levels, commonly leading to yield losses. Further, excessive precipitation, high winds, or producer labor constraints can delay foliar application beyond economically‐optimal thresholds. Insecticide seed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…This technique brings benefits, such as seedling protection and reduction of environmental impacts, but can also bring some limitations (Lamichhane et al 2020). Wheat production without seed treatment dramatically reduces grain yield, making pesticide treatment indispensable (DeVuyst et al 2014;Laminchhane et al 2020). Our results showed that A. brasilense inoculation is compatible with fungicide and insecticide seed dressing, provided that maximum time of four hours between inoculation and sowing is adhered to.…”
Section: Effect Of a Brasilense Inoculation And Wheat Seed Dressing O...mentioning
confidence: 99%
“…This technique brings benefits, such as seedling protection and reduction of environmental impacts, but can also bring some limitations (Lamichhane et al 2020). Wheat production without seed treatment dramatically reduces grain yield, making pesticide treatment indispensable (DeVuyst et al 2014;Laminchhane et al 2020). Our results showed that A. brasilense inoculation is compatible with fungicide and insecticide seed dressing, provided that maximum time of four hours between inoculation and sowing is adhered to.…”
Section: Effect Of a Brasilense Inoculation And Wheat Seed Dressing O...mentioning
confidence: 99%
“…The Federal Insecticide, Fungicide and Rodenticide Act (FIFRA) obligates the EPA to balance between risks and benefits when making pesticide registration decisions . Much of the benefit evidence for neonicotinoid seed treatments has come from small‐plot field experiments examining the impact of neonicotinoids on yields for a variety of crops in the United States . As with all scientific methodologies, small‐plot studies have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Retrieving seed produced in a growing season with high FHB incidence may also have influenced the relatively high yield response to chemical seed treatment in our study, although seed treatments have previously increased grain yield in other studies (Beres et al, 2016;DeVuyst et al, 2014;Pike et al, 1993;Turkington et al, 2016). The chance of achieving a sufficient yield increase to cover the costs associated with seed treatment depends on the treatment costs (Esker and Conley, 2012).…”
Section: Discussionmentioning
confidence: 82%